AGST (Autonomic Grid Simulation Tool): uma ferramenta para modelagem, simulação e avaliação de abordagens autonômicas para grades de computadores - GOMES, Berto de Tácio Pereira (2012)
Computer Grids are characterized by the high dynamism of its execution environment, resources and tasks heterogeneity, and high scalability. These features turn tasks such as configuration, maintenance and failure recovery quite challenging and is becoming increasingly difficult to perform them only by human agents. The autonomic computing term denotes computer systems capable of changing their behavior dynamically in response to changes in the execution environment. For achieving this, the software is generally organized following the MAPE-K (Monitoring, Analysis, Planning, Execution and Knowledge) model, in which autonomic managers perform of the execution environment sensing activities, context analysis, planning and execution of dynamic reconfiguration actions, based on shared knowledge about the controlled system. Several recent research efforts seek to apply autonomic computing techniques to grid computing, providing more autonomy and reducing the need for human intervention in the maintenance and management of these computing environments, thus creating the concept an autonomic grid. This thesis presents a new simulator tool for assisting the development and evaluation of autonomic grid approaches called AGST (Autonomic Grid Simulation Tool). The major contribution of this tool is the definition and implementation of a simulation model based on the MAPE-K autonomic management cycle, that can be used to simulate the monitoring, analysis and planning, control and execution functions, allowing the simulation of an autonomic computing grid. AGST also provides support for parametric and compositional dynamic adaptations of managed elements. This work also presents two case studies where the proposed tool was successfully used for the modeling, simulation and evaluation of approaches to grid computing.